Optimization of biofilm mediated hydrolytic activity of POME for enhanced biogas production - Alam, Md. Zahangir; Fazil, Nurul Alia; Azmi, Azlin Suhaida; Mansor, Mariatul Fadzillah (2018)
Oil palm industry (OPI) in Malaysia generates a huge amount of palm oil mill effluent (POME) during the processing of crude palm oil. One ton of fresh fruit brunch produces 0.5 to 0.7 tonnes of POME. The generation of POME by the OPI has been a serious issue to handle due to its high content of COD and BOD. These wastes need proper treatment to be handled as without proper management it can create significant impact towards the environment. Therefore, anaerobic digestion of POME for enhancement of biogas production could be an effective treatment process for sustainable development. In this study, biogas was produced by anaerobic digestion of POME applying biofilm-based technology. Biofilm mediated hydrolysis of POME was carried out to improve hydrolytic enzyme activity towards faster degradation. 2 grams of granular activated carbon (2.8 mg of biofilm per gram carrier) were added as the carrier to the biofilm into the flask experiment containing raw POME and incubated in room temperature with shaking at 150 rpm rotational speed. Several parameters such as hydrolytic activities, free fatty acid (FFA), sugar content were analyzed to evaluate the biofilm performance. A mixture of two to four strains of isolated bacteria had been proven in the earlier study to have better hydrolytic activity with 75.1% improvement (in terms of lipid hydrolysis) compared to control flask (non-sterilized POME with beads addition). Optimization of hydrolytic activity of POME was done using Design-Expert software, Response surface methodology (RSM) based on face-centered central composite design (FCCCD) was used to optimize two important reaction variables – Total suspended solids (TSS) of POME and amount of carrier employed as compared to the hydrolytic compound production. The optimum condition for hydrolysis of POME has been found to be at TSS of 2% with 2 grams of carrier utilized. Using the hydrolysate, the biogas enhancement was observed by 2-3 folds in the treatment process.